New and little known earthworm species from Central Madagascar (Oligochaeta: Kynotidae) - Csuzdi, Csaba; Razafindrakoto, Malalatiana; Blanchart, Eric (Zootaxa, 2012)
The investigation of a small number of earthworms collected in Central Madagascar resulted in the discovery of two spe-cies new for science, Kynotus minutus and Kynotus parvus spp. nov. Apart from the descriptions and illustrations of thenew species, the two little-known species Kynotus alaotranus Michaelsen, 1907 and Kynotus michaelseni Rosa, 1892 arerecorded for the first time after the original description, and commented short diagnoses are provided. With the two newspecies described in this paper, the genus Kynotus now contains 20 species. The monogeneric earthworm family Kynotidae is endemic to Madagascar.